Kemampuan Adsorpsi Pektin Kulit Buah Kawista (Limonia Acidissima L.) TerhadapoIon Logam Pb2+ dan Aplikasinya pada Limbah Laboratorium Farmasi “X - Ibrahim Arifin Ibrahim; Friska Wijayanti; Khoirul Anwar (JURNAL FARMASI DAN MAKANAN, 2025)
Heavyometals areoone ofothe contents of pharmaceutical laboratory liquid waste. Lead metal can cause poisoning through breathing. Theopurpose0of this study was0toodetermine the optimum conditionsoof kawista fruit skin pectin in absorbing Pb2+ ions against theoparametersoofoweight variationjand contactotimekandkto determine the percentage of Pb2+ ion reduction inopharmaceutical laboratory liquid waste. The pectin isolation method was carried out using the conventional method and pectin characteristics by conducting FTIR identification, testing water content, ash content, equivalentkweight, methoxylocontent, galacturonic content, and degree ofoesterification. Heavyometal adsorptionoabilityotestowith 2 variations,0namely0weight0100,0300,o500omg and contact0time 30, 60,0900minutes. The analysis method used atomicoabsorption0spectrophotometry. Theoresults showed that0theooptimum0weight0occurred0ato5000mg with a decrease in Pb2+ ions of 85.90% and a contact time of 90 minutes of 89.15%. The results of the application of pharmaceutical laboratory waste obtained a percentage reduction in Pb2+ ions of 90.60%. Anova and Kruskall Wallis tests showed differences in the ability to reduce metal ion levels in variations in weight and contact time using kawista skin pectin on pharmaceutical laboratory waste. Then a post hoct test resulted in a significant difference in weight variation and contact time as seen from the significance value <0.05. Keywords: adsorbent, kawista skin pectin, Pb2+, pharmaceutical industry waste.